Answer:
3,672
Step-by-step explanation:
Given the sequence 6, 9, 12...
The sequence is an arithmetic sequence
first term a = 6
common difference d = 9 - 6 = 12 - 9 = 3
number of terms n = 48
Sn = n/2[2a+(n-1)d]
Substitute the given values
S48 = 48/2[2(6)+(48-1)(3)]
S48 = 24(12+(3*47))
S48 = 24(12+141)
S48 = 24(153)
S48 = 3,672
Hence the sum of the first 48terms is 3,672
Answer:
Step-by-step explanation:
so you will move constant to the right side and change the sign. 72x=223-7
then you will subtract the numbers 72x=223-7 and that will give you 72=216
then you will divide both sides by 72 and that will give you
- x=3 .
★ QUADRATIC RESOLUTION ★
Roots of the given equation will be imaginary because it's discriminant is less than 0 and hence it'll yield imaginary solutions
D < 0
b² - 4ac < 0
4² - 4 ( 5 ) < 0
16 - 20 < 0
-4 < 0
Hence it's character is stated above
★✩★✩★✩★✩★✩★✩★✩★✩★✩★✩★
Answer:
10n -10
Step-by-step explanation:
5n * 2n = 10n
-5 * 2 = -10
-10 + 10n = 10n - 10